Craving in Alcohol-Dependent Patients After Detoxification Is Related to Glutamatergic Dysfunction in the Nucleus Accumbens and the Anterior Cingulate Cortex - Bauer, Jochen; Pedersen, Anya; Scherbaum, Norbert; Bening, Johanna; Patschke, Johanna; Kugel, Harald; Heindel, Walter; Arolt, Volker; Ohrmann, Patricia (Neuropsychopharmacology (New York, N.Y.), 2013)
The upregulation of glutamatergic excitatory neurotransmission is thought to be partly responsible for the acute withdrawal symptoms and craving experienced by alcohol-dependent patients. Most physiological evidence supporting this hypothesis is based on data from animal studies. In addition, clinical data show that GABAergic and anti-glutamatergic drugs ameliorate withdrawal symptoms, offering indirect evidence indicative of glutamatergic hyperexcitability in alcohol-dependent subjects. We used proton magnetic resonance spectroscopy to quantify the glutamate (Glu) levels in healthy control subjects and in alcohol-dependent patients immediately after detoxification. The volumes of interest were located in the nucleus accumbens (NAcc) and the anterior cingulate cortex (ACC), which are two brain areas that have important functions in reward circuitry. In addition to Glu, we quantified the levels of combined Glu and glutamine (Gln), N-acetylaspartate, choline-containing compounds, and creatine. The Glu levels in the NAcc were significantly higher in patients than in controls. Craving, which was measured using the Obsessive Compulsive Drinking Scale, correlated positively with levels of combined Glu and Gln in the NAcc and in the ACC. The levels of all other metabolites were not significantly different between patients and controls. The increased Glu levels in the NAcc in alcohol-dependent patients shortly after detoxification confirm the animal data and suggest that striatal glutamatergic dysfunction is related to ethanol withdrawal. The positive correlation between craving and glutamatergic metabolism in both key reward circuitry areas support the hypothesis that the glutamatergic system has an important role in the later course of alcohol dependence with respect to abstinence and relapse.